The Interest and Exam Preferences for Postgraguation of Medical Graduates from a Private Medical College in Lahore who have Completed their one year House Job in 2020 - Riaz, Sidrah; Aqil, Amash; Riaz, Sara; Khan, Muhammad Tariq; Kamal, Zahid; Bano, Norin Iftikhar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective of study: To study the interest and postgraduate exam preferences adopted by young doctors who have successfully completed their one-year house job in May 2020, who graduated from a private medical college of Lahore Place and duration: The data of doctors was collected from records of Akhter Saeed Medical and Dental college Lahore, who had completed their one-year house job from May 2019 to May 2020. Study design: It was a cross sectional survey. Non-probability conventional sample was used. The data was analyzed by SPSS-25 and presented in forms of tables, bar charts and pie charts. Materials& methods: The data of 121 students is collected from college and hospital records who graduated in 2019, started their house job in May 2019 and completed in May 2020. The students who were fail in final professional exam or were not able to complete their house job due to any reason were excluded from study. Each student was contacted in person and required information was collected after verification of their names and roll numbers with their consent. Close ended same set of questions were asked from each student. Data was collected and analyzed by SPSS 25. Results: Total 121 young doctors were included in our study, 81 (66.9%) females and 40 (33.1%) males. Out of theses 63 (52.1%) responded and 58 (47.9%) didn’t. The unviability of getting response was either lack of consent to respond or change of contact numbers. Regarding marital status 32 (50.8%) were unmarried [19 (30.16%) females, 13 (20.63%) males] and 31 (49.2%) were married [20 (31.75%) females ,11 (17.64%) males]. Forty-nine 49 (77.78%) medical graduates actually perused their career and went for some post graduate exams whereas 14 (22.22%) only planned and didn’t appear in any exam after completion of one year house job. Among doctors who responded, eleven 11 (17.5%) young doctors [9 (14.29%) females ,2 (3.17%) males], successfully started their residency after FCPS part l examination, twenty-one 21 (33.3%) were waiting for their induction after passing their FCPS part l exam [13(20.63%) females, 8(12.70%) males], eight 8(12.70%) went for PLAB exam [5 (7.93%) females 3 (4.76%) males] and seven 7 (11.1%) attempted part l exam [5(7.93%) females ,3 (4.76%) males] but not declared successful. The other options perused by doctors for postgraduation were MCPS dermatology 1(0.8%), two years diploma radiology 1 (0.8%), M Phil biochemistry 1 (0.8%), exam of Australian medical council 1 (0.8%) and STEPs 1 (0.8%). There were eleven 11 (17.5%) doctors [5 (7.93%) females ,6 (9.52%) males] who didn’t appear in any exams. The top four favourite specialties preferred by graduates of Akhtar Saeed Medical college were medicine 19 (15.7%), surgery 10 (8.3%), gynecology 7 (5.8%) and anesthesia 3 (2.5%). The remaining were radiology 2 (1.7%), ENT 2 (1.7%), eye 1 (0.8%) and cardiology 1 (0.8%). Conclusion: It was an encouraging, reassuring and promising trend that young graduates from a private medical college pursue postgraduate qualification timely. Most students were females and majority preferred clinical over basic sciences for postgraduation. These young doctors should be guided and trained in those subjects which face shortfall in specialists. The data can help to find job opportunities in Pakistan to avoid brain drain.